2014
DOI: 10.1063/1.4899069
|View full text |Cite
|
Sign up to set email alerts
|

Cyclic voltammetry on sputter-deposited films of electrochromic Ni oxide: Power-law decay of the charge density exchange

Abstract: Porous nickel oxide films were deposited onto unheated indium tin oxide coated glass substrates by reactive dc magnetron sputtering. These films had a cubic NiO structure.Electrochromic properties were evaluated in 1 M potassium hydroxide (KOH) and in 1 M lithium perchlorate in propylene carbonate (Li-PC). Large optical modulation was obtained for ~500-nm-thick films both in KOH and in Li-PC (~70 % and ~50 % at 550 nm, respectively). In KOH, tensile and compressive stress, due to expansion and contraction of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 104 publications
4
26
0
Order By: Relevance
“…Our data agree with prior work which has stated several times that the (111) growth direction tends to be favored when Ni oxide films are produced in the presence of a sufficient amount of oxygen [51][52][53] . are consistent with the morphology of our NiO 1.22 films reported on before [30] . The features observed in the SEM images clearly are larger than the grain sizes indicated by XRD and must consist of several grains.…”
Section: Composition and Structure Of Ni Oxide Thin Filmssupporting
confidence: 81%
See 1 more Smart Citation
“…Our data agree with prior work which has stated several times that the (111) growth direction tends to be favored when Ni oxide films are produced in the presence of a sufficient amount of oxygen [51][52][53] . are consistent with the morphology of our NiO 1.22 films reported on before [30] . The features observed in the SEM images clearly are larger than the grain sizes indicated by XRD and must consist of several grains.…”
Section: Composition and Structure Of Ni Oxide Thin Filmssupporting
confidence: 81%
“…The electrochromism of lithium-containing Ni oxide films has been investigated in numerous studies aimed at elucidating basic optical and electrochemical mechanisms [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] as well as to produce counter electrodes for application in W-oxide-based EC devices [5,27,32,[34][35][36][37][38] .…”
Section: + Exchange In Ni Oxide: a Critical Assessmentmentioning
confidence: 99%
“…5b), which can be described in terms of a power law. 22 Clearly, all Ir-Ni oxide films exhibited remarkable electrochemical stability and withstood at least 10,000 CV cycles. Data for films with γ = 4.5% and γ = 5.5% have initial charge densities similar to that for pure Ni oxide, but the decline rate was much smaller.…”
Section: Charge Density and Electrochromismmentioning
confidence: 99%
“…[15][16][17][18] Ni oxide was put forward as an alternative 19,20 and has been of sustained interest for almost 30 years. We recently demonstrated that the coloration is a surface process 21 and that the degradation of charge density in Ni oxide obeys a power law 22 upon cycling in a Li-conducting electrolyte, which implies that a monotonic decline of the optical properties takes place and eventually leads to device failure. Many studies during the last years have focused on ways to improve the performance of Ni oxide films with regard to optical modulation speed and span, bleachedstate transmittance and electrochemical cycling durability by use of additives such as Li, [23][24][25] C, 26, 27 N, 28 F, 29 Al, 30 Ti, 31, 32 V, 33,34 Mn, 35 Co, 36 Cu, 37 W, 38,39 (Li,W), 40 (Li,Al), 41 (Li,Zr), 42 and LiPON.…”
Section: Introductionmentioning
confidence: 99%
“…The following methods are commonly employed in experimental works: pulse laser deposition [11], vacuum sputtering [12], chemical bath deposition [13], sol-gel process [14], spray pyrolysis [15], etc. The main disadvantage of previously listed methods is the difficulty of implementation in the production process of electrochromic devices.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%